The Influence of Device Access and Gender on Children's Reading Frequency - Roni, S.; Merga, Margaret (Routledge, 2017)
We explore the role that devices currently play in children's book reading, finding that while children have relatively high access to devices with eReading capability, these devices are underutilised for reading purposes. While ownership of devices was negatively associated with reading frequency for both genders, its negative impact was more significant for girls than boys. We also found that when boys and girls identified themselves as daily readers, and where they had access to devices, they did not use them frequently for book reading, suggesting that paper book reading is still preferable for frequent book readers of both genders.